Systematic Literature Review Application of Expressive Writing Techniques for Victims of Bullying in Indonesia - Tririzky, Reza; Firman, Firman; Afdal, Afdal (Universitas Negeri Padang, 2024)
The phenomenon of bullying brings and has a profound effect on the victims who experience it. This condition affects the victim's living conditions in various aspects of conditions that are not only limited to physical, but more referring to and affecting the psychological condition of the victim. The purpose of this study is to identify the application of expressive writing techniques for victims of bullying from publications in Indonesia. Furthermore, a systematic literature review research was applied using the PRISMA method to fulfill the research objective. Data collection was conducted through digital tracking from a trusted source, Google Scholar. After the tracking and selection process, 10 studies were collected that discussed the use of expressive writing techniques and bullying victims in Indonesia. It was found that most of the results showed that expressive writing techniques have been applied to victims of bullying. However, it is still limited to anxiety problems.